Analysis of Leadership Style and Employee Work Discipline in Improving Organizational Performance - Rusdin Ndua; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Journal of Educational Management Research, 2025)
This study examines the relationship between the Village Head's leadership style and employee work discipline at the Padang Tumbuo Village Office, Ampana Kota District, Tojo Una-Una Regency. Quality human resources (HR) are crucial in achieving organizational goals, particularly in the public sector. This study employed a qualitative design with a case study approach, with data collected through in-depth interviews and direct observation. The results indicate that the Village Head's democratic-participatory leadership style, with directive and transformational touches, plays a significant role in improving employee work discipline. The Village Head provides appreciation, motivation, and direct involvement in work activities, creating a positive work atmosphere. However, challenges remain in discipline, such as tardiness and a lack of understanding of duties and responsibilities. This study suggests the importance of regular training, a more effective attendance system, and objective performance evaluation. The contribution of this study is to enrich the literature on the influence of leadership style on employee discipline in village government.